Knowledge, attitudes and adapted behaviours of adults with Type 2 Diabetes Mellitus, attending a private clinic in the Western Cape: A mixed-method study. - Winton, Loreen (Stellenbosch : Stellenbosch University, 2020)
Thesis (MHumanRehabSt)--Stellenbosch University, 2020.